Use of Clodronate Liposomes to Deplete Phagocytic Immune Cells in Drosophila melanogaster and Aedes aegypti - Ramesh Kumar, Jyothsna; Smith, Jessica P.; Kwon, Hyeogsun; Smith, Ryan C. (Frontiers in Cell and Developmental Biology, 2021)
The innate immune system is the primary defense response to limit invading pathogens for all invertebrate species. In insects, immune cells are central to both cellular and humoral immune responses, however few genetic resources exist beyond Drosophila to study immune cell function. Therefore, the development of innovative tools that can be widely applied to a variety of insect systems is of importance to advance the study of insect immunity. Here, we have adapted the use of clodronate liposomes to deplete phagocytic immune cells in the mosquito, Aedes aegypti, and the vinegar fly, Drosophila melanogaster. Through a variety of microscopy and molecular techniques, we validate the depletion of phagocytic cell populations in both insect species and demonstrate the integral role of phagocytes in combating bacterial pathogens. Together, these data demonstrate the wide utility of clodronate liposomes in insect systems to advance the study of phagocyte function in insect innate immunity.